Current concepts in elbow fracture dislocation. (August 2021) - Watts, Adam C; Singh, Jagwant; Elvey, Michael; Hamoodi, Zaid
Background: Elbow fracture dislocations are complex injuries that can provide a challenge for experienced surgeons. Current classifications fail to provide a comprehensive system that encompasses all of the elements and patterns seen in elbow fracture dislocations. Methods: The commonly used elbow fracture dislocation classifications are reviewed and the three-column concept of elbow fracture dislocation is described. This concept is applied to the currently recognised injury patterns and the literature on management algorithms. Results: Current elbow fracture dislocation classification systems only describe one element of the injury, or only include one pattern of elbow fracture dislocation. A new comprehensive classification system based on the three-column concept of elbow fracture dislocation is presented with a suggested algorithm for managing each injury pattern. Discussion: The three-column concept may improve understanding of injury patterns and treatment and leads to a comprehensive classification of elbow fracture dislocations with algorithms to guide treatment.